Influence of weak injection on spatiotemporal instabilities in a broad-area vertical-cavity semiconductor laser - E.A. Yarunova; A.A. Krents; N.E. Molevich (Компьютерная оптика)
The dynamics of a broad-area vertical-cavity semiconductor surface-emitting laser (VCSEL) is theoretically investigated with due regard for the Henry factor. A linear analysis of the stability of a spatially homogeneous lasing regime is performed and the modulation instability is shown to develop in such lasers. The minimum size of the aperture at which the instability of the optical field begins to develop is determined. The results are confirmed by the numerical solution of a system of differential equations. It is shown that the suppression of the modulation instability can be achieved by injecting into the resonator an external low-amplitude optical radiation.